Evaluation of four commercial severe acute respiratory coronavirus 2 antibody tests. Issue 7 (July 2021) - Ashizawa, Nobuyuki; Takazono, Takahiro; Ohyama, Kaname; Nagasaki, Yoji; Okamoto, Masaki; Hirayama, Tatsuro; Takahashi, Kensuke; Yamanashi, Hirotomo; Tashiro, Masato; Hosogaya, Naoki; Tanaka, Takeshi; Yamamoto, Kazuko; et al.
Abstract: Introduction: Numerous severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) serological tests exists commercially; however, their performance using clinical samples is limited. Although insufficient to detect SARS-CoV-2 in the early phase of infection, antibody assays can be of great use for surveillance studies or for some coronavirus disease 2019 (COVID-19) patients presenting late to the hospital. Methods: This study evaluated the sensitivity and specificity of four commercial SARS-CoV-2 lateral flow antibody tests using 213 serum specimens from 90 PCR-positive confirmed COVID-19 patients. Of 59 negative control sera, 50 were obtained from patients with other respiratory infectious diseases before COVID-19 pandemic began while nine were from patients infected with other respiratory viruses, including two seasonal coronaviruses. Results: The varied sensitivities for the four commercial kits were 70.9%, 65.3%, 45.1%, and 65.7% for BioMedomics, Autobio Diagnostics, Genbody, and KURABO, respectively, between sick days 1 and 155 in COVID-19 patients. The sensitivities of the four tests gradually increased over time after infection before sick day 5 (15.0%, 12.5%, 15.0%, and 20.0%); from sick day 11–15 (95.7%, 87.2%, 53.2%, and 89.4%); and after sick day 20 (100%, 100%, 68.6%, and 96.1%), respectively. For severe illness, the sensitivities were quite high in the late phase after sick day 15. The specificities were over 96% for all four tests. No cross-reaction due to other pathogens, including seasonal coronaviruses, was observed. Conclusions: Our results demonstrated the large differences in the antibody test performances. This ought to be considered when performing surveillance analysis.